Dialogische Autorität. Feministisch-theologische Überlegungen zur kanonischen Schriftauslegung. (lectio difficilior, 2005)
The canonical approach can be seen as a challenge for feminist theology. This paper tries to find a positive way of looking at the canon in concentrating on the space within the canonical boundaries as a dialogic and polyphonic room. In laying emphasis on the link between text and community the canonical approach cannot suspend the issue of power concerning both text and community.